Characteristic of Patients Undergoing Initiation of Emergency Haemodialysis at Ngoerah Hospital Denpasar in 2023 - Dwi Saraswati, Kadek Sinta; Kandarini, Yenny (Indonesian Journal of Kidney and Hypertension, 2026)
Background: Initiation of emergency hemodialysis is associated with higher morbidity and mortality compared to planned hemodialysis. Identifying the characteristics of patients undergoing emergency hemodialysis is essential to improve clinical outcomes. This study aimed to describe the clinical characteristics of patients who initiated emergency hemodialysis at Ngoerah Hospital, Denpasar, in 2023. Methods: This cross-sectional descriptive study used secondary data obtained from the patient registry. Total sampling was applied to include all patients who underwent initiation of emergency hemodialysis at Ngoerah Hospital, between January 1 and March 31, 2023. Data were analyzed descriptively. Results: A total of 70 patients were included. The mean age was 54.54 ± 14.6 years, and 52.3% were male. The most common etiology of CKD) was obstructive nephropathy (32.8%), followed by diabetic kidney disease (21.4%). Major comorbidities included heart disease (35.7%), malignancy (25.8%), and diabetes mellitus (21.4%). The most frequent indications for emergency hemodialysis were metabolic acidosis (71.8%). Temporary jugular vein central venous dialysis catheters were the most commonly used vascular access (67.6%). Only 21.1% of patients had received pre-dialytic monitoring. The median estimated glomerular filtration rate (eGFR) was 5.69 mL/min/1.73 m², median serum creatinine was 8.47 mg/dL, and median serum potassium level was 5.6 mEq/L. Conclusion: Patients initiating emergency hemodialysis at Ngoerah Hospital demonstrated diverse clinical characteristics. The high prevalence of metabolic acidosis along with low rates of pre-dialytic monitoring, highlights the need for improved early detection and management of CKD to reduce emergency hemodialysis initiation. Keywords: emergency hemodialysis, patient characteristics, chronic kidney disease, Ngoerah Hospital Denpasar